Al-‘Ulama Warasatul Anbiya: Theological Leadership, Wasatiyyah (Modernization) in Advancing Sustainable Development Goals (SDGs) - Mohammad Eisa Ruhullah; Thameem Ushama; Nurul Ain Binti Norman (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to examine the evolving role of the ‘Ulama as theological leaders within the framework of Al-‘Ulama Warasatul Anbiya, focusing on the integration of Wasatiyyah (Islamic moderation) in Islamic political governance to support the achievement of the Sustainable Development Goals (SDGs). Historically, the ‘Ulama have distanced themselves from direct political involvement to preserve religious authority and avoid governance entanglements. However, this approach has often created a disconnect between the ‘Ulama and society, diminishing the relevance of religious leadership in addressing contemporary political and societal challenges. Theoretical framework: The theoretical framework of this study draws on classical and modern Islamic political thought, particularly Ibn Taymiyyah’s Siyasah Shariyah, which emphasizes public trust (Amanah), cooperation (Ta'awun), and consultation (Shura). Literature Review: Previous literature highlights criticism of the reluctance of the ‘Ulama to reinterpret Islamic teachings in light of contemporary realities, which is seen as weakening their theological authority. Methods: This research employs qualitative methods, combining historical analysis and case studies. The data is critically analyzed to evaluate the role of the ‘Ulama in integrating Wasatiyyah into modern Islamic political governance. Results: The findings reveal that the Wasatiyyah approach provides a balanced framework for maintaining religious integrity while engaging in socio-political issues. The future relevance of the ‘Ulama depends on their ability to address modern challenges while upholding Islamic ethical values, guided by Maqasid al-Shari'ah (the higher objectives of Islamic law). Implications: The implications of this research suggest that active participation of the ‘Ulama in moderate political governance can enhance the role of religion in supporting SDGs, particularly in fostering just and inclusive governance. Novelty: The novelty of this study lies in the integration of Wasatiyyah and Maqasid al-Shari'ah as an operational framework to address contemporary political and societal challenges.